Pengaruh Islamic Branding, Literasi Keuangan Syariah dan Service Quality Terhadap Keputusan Menjadi Nasabah Bank Syariah Indonesia di Kabupaten Aceh Barat - Wulan Dari Puspita; Muzakir Muzakir (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2025)
This consider points to decide the impact of Islamic Branding, Islamic money related education and benefit quality on people's choices to gotten to be clients of Bank Syariah Indonesia, West Aceh Rule. This ponder could be a quantitative consider. The test in this think about was 96 clients of Bank Syariah Indonesia, West Aceh Rule. This ponder employments essential information related to the character of the respondents, as well as the respondents' recognitions of Islamic Branding, Islamic budgetary proficiency and benefit quality on people's choices to ended up clients. The investigation utilized in this ponder is different direct relapse investigation. The results of this ponder demonstrate that 1) there's an impact of Islamic Branding on people's choices to ended up clients, 2) there's an influence of Islamic budgetary education on people's choices to gotten to be clients, 3) there's an impact of benefit quality on people's choices to ended up clients, 4) at the same time Islamic Branding, Islamic money related education and benefit quality on people's choices to gotten to be clients of Bank Syariah Indonesia Rule have a positive and critical impact on people's choices to gotten to be clients of Bank Syariah Indonesia, West Aceh Rule, with the Fcount esteem (24.775) more prominent than Ftable (3.095) and the importance esteem is 0.000.